2014
DOI: 10.1098/rspb.2013.3019
|View full text |Cite
|
Sign up to set email alerts
|

Island tameness: living on islands reduces flight initiation distance

Abstract: One of Darwin's most widely known conjectures is that prey are tame on remote islands, where mammalian predators are absent. Many species appear to permit close approach on such islands, but no comparative studies have demonstrated reduced wariness quantified as flight initiation distance (FID; i.e. predator-prey distance when the prey begins to flee) in comparison with mainland relatives. We used the phylogenetic comparative method to assess influence of distance from the mainland and island area on FID of 66… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
109
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(112 citation statements)
references
References 48 publications
2
109
1
Order By: Relevance
“…Unlike predators (e.g. wolves and tigers), which have been historically configured in terms of 'disgust/fear' (Emel 1995), giant tortoises and in general Galapagos' wildlife, has been historically and ecologically recognized as 'tame' and gentle (Cooper et al 2014). Although this could be similar for example with the recent case of the white rhino in South Africa (Brooks 2006), the difference is the time people had to develop a particular stance towards a specie (i.e.…”
Section: Galapagos Case Vis-a-vis Other Iconic Species Conservation Cmentioning
confidence: 99%
“…Unlike predators (e.g. wolves and tigers), which have been historically configured in terms of 'disgust/fear' (Emel 1995), giant tortoises and in general Galapagos' wildlife, has been historically and ecologically recognized as 'tame' and gentle (Cooper et al 2014). Although this could be similar for example with the recent case of the white rhino in South Africa (Brooks 2006), the difference is the time people had to develop a particular stance towards a specie (i.e.…”
Section: Galapagos Case Vis-a-vis Other Iconic Species Conservation Cmentioning
confidence: 99%
“…This suggests that FID in horses, whether directly or indirectly through correlation with other risk aversion traits, could be influenced by predation risk. However, whether this pattern holds across populations, as seen in other species (Cooper et al 2014), remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…This finding opens the door to a number of additional analyses in the study population, including testing for the presence of additive genetic variance for FID and genetic correlations with other traits (Wilson and Poissant 2016), as well as the presence of negative directional selection as predicted for populations inhabiting predator-free islands (Cooper et al 2014;Brock et al 2015). Although additional research will be necessary to confidently identify drivers and consequences of observed temporal and spatial variation in FID, results clearly indicate that foals in the east have greater FIDs than those in the west.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations